EPAS1 knockdown is associated with cell cycle and DNA replication programs and MYC/E2F-related signatures in hemangioma endothelial cells - Zheren Su; Luying Wang; Ruixue Zhao; Zhiyu Li; Jing Li; Jianhai Bi; Ran Huo (PLoS ONE, 2026)
Infantile hemangioma (IH) is the most common benign tumor of infancy. Hypoxia and activation of hypoxia-inducible factor (HIF) signaling have been proposed to contribute to IH pathogenesis, yet the role of endothelial PAS domain-containing protein 1 ( EPAS1 ), which encodes hypoxia-inducible factor-2α (HIF-2α), in hemangioma endothelial cells (HemECs) remains less well characterized. Here, we investigated HIF-2α in primary HemECs using a pharmacological inhibitor (PT-2399) and shRNA-mediated EPAS1 knockdown under normoxic and hypoxic conditions. In hypoxic cultures, PT-2399 treatment was associated with reduced migration and invasion and with a reduction in junction number in tube formation assays; at the selected dose, PT-2399 did not significantly reduce cell viability. By contrast, EPAS1 knockdown was associated with reduced proliferative capacity and altered cell cycle distribution, together with enrichment of DNA replication/cell cycle-related transcriptional programs, negative enrichment of MYC- and E2F-related gene sets, and directionally consistent protein level changes in selected regulators. EPAS1 knockdown-associated phenotypic trends were broadly similar under normoxia and hypoxia, with no clear evidence that hypoxic stimulation enhanced the magnitude of these changes. In IH tissue transcriptomic data, Egl-9 family hypoxia-inducible factor 3 ( EGLN3 ) showed reduced expression, consistent with a testable hypothesis that hypoxia-independent mechanisms may contribute to maintenance of HIF-2α activity in this context. This study is limited by the use of HemECs derived from a single IH specimen and by the absence of on-target validation; accordingly, the findings should be interpreted as exploratory and hypothesis-generating.